2007
DOI: 10.1590/s1517-83822007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between API 20 STREP and multiplex PCR for identification of Enterococcus spp. isolated from Brazilian foods

Abstract: We evaluated the suitability of API 20 STREP and multiplex PCR to speciate 52 Enterococcus spp. obtained from Brazilian foods. A high percentage of isolates (78.9%) presented discrepant results between evaluated tests. Similar results were obtained for six E. faecalis and five E. faecium. The PCR multiplex was more effective than API 20 STREP for complete identification of the isolates. 3633-1936. E-mail: edemarti@usp.br Enterococci are commonly found in soil, water, plants, vegetables and foods (6,9).This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…It also misidentified 2.7% of the Enterococcus species. Our findings were in agreement with the results of previous studies [ 42 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It also misidentified 2.7% of the Enterococcus species. Our findings were in agreement with the results of previous studies [ 42 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Although API 20 strep is considered the best identification system for bacteria [ 41 ], it does not accurately identify some species of Enterococci [ 42 ]. In the present study, we validated API 20 strep results using PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, the aac(6Ј)-Ii probe on our Enteroarray further confirms and supports the accuracy of the four taxonomic probes in properly identifying E. faecium isolates misidentified by the API 20 Strep method. The intrinsic low-level vancomycin resistance observed in E. gallinarum and E. casseliflavus conferred by the vanC1 and vanC3 genes, respectively, has become a species-specific characteristic and is commonly used as a molecular marker for their identification (5,22,54). All isolates in our study identified as E. gallinarum and E. casseliflavus by the Enteroarray, including the two ATCC strains, possessed either the vanC1 or the vanC3 gene.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, up to 15.8% of the strains of E. faecium were misidentified based on phenotypic methods (15). Another study indicated that PCR-based techniques are more effective than biochemical methods for the complete identification of enterococcal isolates (22). Overall, the studies emphasize the inadequacy of phenotypic methods alone for the correct identification of Enterococcus species, particularly E. faecium.…”
Section: Discussionmentioning
confidence: 68%